PENTINGNYA PENGETAHUAN PAJAK DAN SOSIALISASI PAJAK KEPADA CALON WAJIB PAJAK MASA DEPAN - Rusli, Yohanes Mardinata; Nainggolan, Piter (Jurnal Pengabdian dan Kewirausahaan, 2021)
Taxation is the most important state revenue. This can be seen in the posture of the 2020 and 2021 RAPBN (Drafted State Revenue and Expenditure Budget), where in the 2020 State Budget the state revenue is 2,233.2 trillion and 1,865.7, which is equivalent to 83.53%, which is the target of domestic revenue which is comes from taxation sector revenues. Only 16.47% of the targeted state revenue comes from non-tax revenues. Therefore, the importance of taxation is introduced and socialized early on by the taxation authority in Indonesia, namely The Directorate General of Taxes, Finance Ministry of the Republic Of Indonesia (DGT, Ministry Of  Finance, RI). This is mandatory because there are still many general public as taxpayers who still do not have awareness of the importance of this taxation. From the data in the 2019 Annual Report of the DGT of the Ministry Of Finance of the Republic of Indonesia, It can be seen that the ratio of  of taxpayer compliance in Indonesia to compliance in the submission of tax returns (SPT ) Annual Tax in 2019 for Individual Taxpayers (WPOP) the compliance ratio of both employees and non-employees is 73.23% and 75.93%, this figure is still far from the maximum compliance level of Individual Taxpayers to be achieved by Government. Therefore, real action is needed from the Directorate General of Taxes, Finance Ministry of The Republic Of Indonesia (DGT, Finance Ministry of The Republic Of Indonesia) to carry out tax counseling activities in collaboration with the academic community Which Is included in the strategic planning of the  DGT of Finance Ministry of The Republic Of Indonesia in 2019, namely theme Of increasing tax knowledge and  skills where the target is future taxpayers are students who are in high school (SMU). This activity has been carried out by the DGT of Finance Ministry of Republic Of Indonesia in collaboration with several educational institutions, both schools and universities, of which in 2019 there were 1,092 prospective taxpayers (Class X-XII SMA). Therefore, Bunda Mulia University as one of the higher education institutions that has a Tax Center and cooperates and is under Guidance of tthe DGT of Finance Ministry of Republic Of Indonesia, in this case the North Jakarta Regional Tax Office, participates in supporting outreach activities carried out by the  DGT of Finance Ministry of Republic Of Indonesia by conducting Community Service activities. . This PKM activity was carried out for class XI students at SMK Budi Asih and class XII students at SMK Dharmasava with online through the media google meeting (G-meet) on February 15, 2021, considering that the current COVID-19 pandemic condition in Indonesia and the world makes PKM activities impossible. done face to face. Furthermore, as many as 53 PKM participants who were individuals who attended SMK Budi Asih, participated in this PKM activity. As for after the PKM activity was held, the authors hope that all individuals who attend SMK Budi Asih can better understand the importance of tax knowledge and tax socialization to ensure that these students, who are prospective future taxpayers, can become obedient taxpayers, so that revenue from the taxation sector which is the main state revenue can be met with the target of state revenue.